BLACK BOX TESTING BOUNDARY VALUE ANALYSIS PADA APLIKASI SUBMISSION SYSTEM - kartiko, condro (STKIP PGRI Sumatera Barat, 2020)
Organizing a scientific conference activity is an opportunity for researchers to meet and share research or study that is being done. One of the most important parts of conducting a scientific conference is the process of submission and review paper sent by researchers. The process of using a submission system on a website requires many menus and features that must be available. However, in making a website there are often errors in the interface, submission system, task orientation, submit login, submit sign-up, writing, content quality, page layout, visual design, help and error tolerance. In the following research, applying to test using black-box testing boundary value analysis techniques. Boundary Value Analysis method is a way of testing by determining the value of the lower and upper limits of the data to be tested. This test is performed on the submission system function on the CENTIVE website. The test results show that there are still many shortcomings when validating data that will be input so that it can cause data stored in the database does not match the expected data. Test results can be used as input to improve the system.